CDX2 expression in the hematopoietic lineage promotes leukemogenesis via TGFβ inhibition. Issue 9 (26th June 2021) - Galland, Ava; Gourain, Victor; Habbas, Karima; Güler, Yonca; Martin, Elisabeth; Ebel, Claudine; Tavian, Manuela; Vallat, Laurent; Chenard, Marie‐Pierre; Mauvieux, Laurent; Freund, Jean‐Noël; Duluc, Isabelle; et al.
Abstract : The intestine‐specific caudal‐related homeobox gene‐2 ( CDX2 ) homeobox gene, while being a tumor suppressor in the gut, is ectopically expressed in a large proportion of acute leukemia and is associated with poor prognosis. Here, we report that turning on human CDX2 expression in the hematopoietic lineage of mice induces acute monoblastic leukemia, characterized by the decrease in erythroid and lymphoid cells at the benefit of immature monocytic and granulocytic cells. One of the highly stimulated genes in leukemic bone marrow cells was BMP and activin membrane‐bound inhibitor ( Bambi ), an inhibitor of transforming growth factor‐β (TGF‐β) signaling. The CDX2 protein was shown to bind to and activate the transcription of the human BAMBI promoter. Moreover, in a leukemic cell line established from CDX2‐expressing mice, reducing the levels of CDX2 or Bambi stimulated the TGF‐β‐dependent expression of Cd11b, a marker of monocyte maturation. Taken together, this work demonstrates the strong oncogenic potential of the homeobox gene CDX2 in the hematopoietic lineage, in contrast with its physiological tumor suppressor activity exerted in the gut. It also reveals, through BAMBI and TGF‐β signaling, the involvement of CDX2 in the perturbation of the interactions between leukemia cells and their microenvironment. Abstract : Abnormal expression of the homeodomain transcription factor caudal‐related homeobox gene‐2 (CDX2) is associated with poor prognosis of leukemia patients. Here, we report that turning on human CDX2 expression in the hematopoietic lineage of mice induces acute monoblastic leukemia, through inhibition of the lymphocytic lineage and accumulation of immature monoblasts mediated by the stimulation of the BMP and activin membrane‐bound inhibitor that blocked transforming growth factor‐β‐dependent differentiation of monocytes.